Speculation about the Future of Capitalism - Fatehi, Kamal (Mercados y Negocios, 2021)
The future is unknown. Discussing possible future events cannot provide any evidence to support it. An argument without evidence is merely conjecture and speculation. However, in speculation, we can use existing and past patterns of events to suggest the direction of possible future affairs. This paper speculates on the future changes that capitalism may take. In so doing, it uses past and present developments in sciences and the changing values. It offers two possible scenarios. The first scenario is an optimistic one, and the second is not very optimistic. One could even say it is a pessimistic prediction.